Strategi Lembaga Keuangan Syariah Dalam Menghadapi Tantangan Regulasi dan Persaingan Pasar Global : Analisis Kepatuhan Syariah dan Inovasi Produk - Elvia Ghina Nismara; Yasmin Safinatunnajah; Linda Rose Rohidah; Ika Sahwa Damayanti; Zukrufi Ashof Almaunah; Diana Setiawati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This researchaims to analyze the strategies implemented by Sharia Financial Institutions(SFIs) in maintaining compliance with Islamic law principles amidnational and international regulatory dynamics, as well as examining efforts toadjust products and services to remain competitive in the global market. Using a qualitative descriptive method based on secondary data through a literature review, this study explores regulatory harmonization, sharia compliance mechanisms, product innovation, and improving the quality of human resources askey factors in facing global challenges. The results showthat LKS implement various strategies such as harmonizing Sharia standardswith international provisions, strengthening the role of the Sharia Supervisory Board (DPS),digitizing services, and innovating Sharia-based products. In addition,improving SDI competency through training, certification, and institutional cooperationis an important effort in maintaining competitiveness without neglectingsharia principles. This study concludes that the strategies and innovationscarried out by LKS are complementary in ensuring sharia compliancewhile strengthening the position of the sharia financial industry in the global market. Keywords: Sharia Financial Institutions, Sharia Compliance, National and International Regulations, Product Innovation, Human Resources, Global Market